Correction: Using anion recognition to control the folding and unfolding of a single chain phosphorescent polymer. Issue 69 (16th August 2017) - Ji, Xiaofan; Guo, Chenxing; Ke, Xian-Sheng; Chi, Xiaodong; Moore, Matthew D.; Sessler, Jonathan L.
Abstract : Correction for 'Using anion recognition to control the folding and unfolding of a single chain phosphorescent polymer' by Xiaofan Ji et al., Chem. Commun., 2017, 53, 8774–8777.